Role of ICT investment and diffusion in the economic growth: A threshold approach for the empirical evidence from Pakistan - Habib Ur Rahman; Ghulam Ali; Umer Zaman; Carlo Pugnetti (International Journal of Financial Studies, 2021)
This study investigates the role of Information and Communication Technologies (ICT) investment and diffusion on Pakistan's economic growth by proposing the threshold level of ICT investment. At our proposed level, the ICT imports significantly enhance the intermediate inputs to capital goods, ultimately enhancing economic growth. For this empirical investigation, we use the maximum available data on technological innovation and investment, ranging from 2003 to 2018. Incorporating the structural breaks, the results of regression analysis reveal that Pakistan's economic growth is unaffected by ICT development. However, we observe the mixed shreds of evidence on the ICT investment. Following existing literature, we use ICT goods exports and imports as a proxy for ICT investment. Interestingly, the economic growth of Pakistan is again unaffected by the ICT goods exports. However, we observe that a one percent increase in ICT goods imports enhances economic growth by 1.73 percent. Then, we extend this analysis to the threshold approach, which reveals that ICT imports affect the overall economic growth when the ICT goods imports reach the level of 4.13 percent of the total imports. At this threshold, the ICT goods import significantly enhances the intermediate input to the capital goods, leading to higher economic growth. Therefore, the policymakers should ensure that the ICT goods import must be greater than the 4.13 percent of Pakistani imports.
Keywords: 330; economic growth; ICT; technological innovation; threshold level